Dynamic Governance Capability Modeling in Sidomulyo Village, Jember Regency - Dina Suryawati; Hari Karyadi; Muhammad Zefri Kudus (Universitas Muhammadiyah Jember Press, 2025)
The research discusses the Digital Village program implemented by the Sidomulyo Village Government in Jember Regency. The digital village initiative is realized through the development of a digital village governance system that provides administrative services, disaster mitigation, an online marketplace, and a community complaint platform. In developing this digital governance system, the Sidomulyo Village Government collaborates with partners from the education sector, private sector, and local communities. Named